Effect of Rutin on the Histological Structure of the Heart and Some Biochemical Indicators of Oxidative Stress in Male Albino Rats - Muhammad Fadhel Al Hussani, Aseel Najah Sabour (Pakistan Journal of Medical & Health Sciences, 2022)
The current study aimed to know the effect of rutin at a dose of (30 mg/kg of body weight) and (60 mg/kg of body weight) on heart tissues in two groups of normal rats and two groups of rats exposed to oxidative stress with 1% hydrogen peroxide for the duration of the experiment., as well as the effects of rutin on the percentage of some antioxidants such as glutathione GSH, and the percentage of malonaldehyde (MDA) in the serum. (48) male rats were used, they were divided into six groups.: the first group (control) included eight males, and the second group hydrogen peroxide H2O2 1%, H2O2, and rutin at a concentration of 60 mg/kg, H2O2 with a concentration of rutin 30 mg/kg, and with a concentration of rutin at a concentration of 60 mg/kg and with a concentration of 30 mg/kg of rutin. All groups dosed daily for one month, after taking blood samples, sacrificing the animals, and making tissue sections of the heart under study. The results revealed that Rutin increased the GSH glutathione ratio in the groups in which oxidative stress was induced by hydrogen peroxide by 1% compared to the control group treated with hydrogen peroxide only. While rutin reduced MDA in the same groups compared to the control group that was treated with hydrogen peroxide by only 1%. At (P≤ 0.05) The histological study of the heart of mice treated with Rutin revealed a high cure rate, as Rutin showed protection of the heart tissue from the toxicity caused by hydrogen peroxide. While the tissue sections of the positive control group that were treated with 1% hydrogen peroxide showed clear tissue degeneration with hemorrhage and necrosis. The histological results of two groups treated with concentrations of (30 mg/kg of body weight) and (60 mg/kg of body weight) showed no toxic effects of rutin compared with the negative control group. Keywords: Rutin, heart, GSH, MDA